UNIFICATION OF ACCOUNTING METHODOLOGY: THE PROBLEM OF CORRELATION BETWEEN THE CONCEPT OF MULTIVARIANCE AND COMPARABILITY OF FINANCIAL STATEMENTS - N. Adintsova; E. Zhuravleva (Вестник Северо-Кавказского федерального университета, 2022)
The article is devoted to a discussion of the nature of the existence of a direct connection between the multivariate methodology and the comparability of financial statements, where the importance of consistency in national accounting standards should lead to comparability of financial data, resulting in to improve the latter required regulation methodology by reducing the number of alternatives given in the accounting standards.